Multidimensional Comparisons of Health Systems Functioning in OECD Countries - Pacáková, Viera; Papoušková, Monika (My University, 2016)
Objective of the article is comparison of health care status and functioning of health systems in OECD countries, depending on risk factors, health expenditures, and health care resources and activities using appropriate multidimensional statistical methods. There are significant differences in health and healthcare results between and within OECD countries and regions. Article aims to present the results of application of multivariate statistical methods, namely factor analysis, cluster analysis and multidimensional comparative methods which provide an overview of the health care status and public health systems expenditures, various causal relations and differences or similarities of the OECD countries. This information is essential to the development of national and international health policies for treatment and financial budget of public health systems.
Multidimenzionální srovnání zdravotních systémů fungujících v zemích OECD
Keywords: Comparison; health care; health expenditure; health systems; health status; multidimensional methods; risk factors.; Porovnávání; zdravotní péče; náklady na zdravotnictví; zdravotní systémy; zdravotní stav; vícerozměrné metody; rizikové faktory.